2020
DOI: 10.1002/jcp.29499
|View full text |Cite
|
Sign up to set email alerts
|

HOXB‐AS1 accelerates the tumorigenesis of glioblastoma via modulation of HOBX2 and HOBX3 at transcriptional and posttranscriptional levels

Abstract: Glioblastoma (GBM) is the most universal and invasive brain tumor among adults. Increasing studies have reported that long noncoding RNAs play vital roles in regulating downstream molecules at the transcriptional or posttranscriptional level in tumor progression. The purpose of the current research was to inquire the modulation mechanism by which homeobox B cluster antisense RNA 1 (HOXB-AS1) functioned in GBM. Our study first discovered the lifted expression of HOXB-AS1 and its nearby genes HOXB2 and HOXB3 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…For Long non-coding RNAs (lncRNAs), as one of the key regulators of cancer, function not only as important molecular markers for cancer prognosis, but also as markers of molecular characteristics at the pan-cancer level. Increasing studies have shown that several lncRNAs affect cancer tumorigenesis and contribute to cancer pathogenesis (Akbari et al, 2020;Bi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For Long non-coding RNAs (lncRNAs), as one of the key regulators of cancer, function not only as important molecular markers for cancer prognosis, but also as markers of molecular characteristics at the pan-cancer level. Increasing studies have shown that several lncRNAs affect cancer tumorigenesis and contribute to cancer pathogenesis (Akbari et al, 2020;Bi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Han et al (2020 ) also found that FAM83H-AS1 is associated with triple-negative BC progression by regulating miR-136-5p and MTDH expression. LncRNA HOXB-AS1 can promote the proliferation, migration, and invasion of glioblastoma cells ( Bi et al, 2021 ), multiple myeloma ( Chen R. et al, 2020 ), and endometrial carcinoma ( Liu et al, 2020 ). However, it is less studied in BC.…”
Section: Discussionmentioning
confidence: 99%
“…Another antisense lncRNA that exerts its function at the transcriptional level is HOXB-AS1 . In glioblastoma (GBM), increased expression of HOXB-AS1 promotes proliferation and induces apoptosis by recruiting transcription factor ILF3 to the promoter regions of HOBX2 and HOBX3 [ 43 ].…”
Section: Transcriptional Modulationmentioning
confidence: 99%